Case Study, Character Analysis And Development Of Students - Jusman Tang; Fenny Hasanuddin; Syahrir L; Nadirah Nadirah (La Ogi : English Language Journal, 2023)
In the world of education, teaching and learning activities are not only intended to make students know knowledge academically, but also will build student character, so that in this case character education is considered very important to be carried out in formal and non-formal schools. Students with good and noble characters will be able to live their lives more interestingly in the future . Each person has character individually . understanding This character can also be misinterpreted by the character, personality and traits that a person has. Actually the definition of character itself is an accumulation of character, personality and traits that a person has. Character in a person is actually formed indirectly from the learning process that goes through , the character of a person does not come from something innate but rather from the formation of the environment to the people who are near him . in shape realize education good character , schools need to anchor the values of social norms through each activity at school . Based on results research conducted at SMPN 3 Dua Pitue with do interview development character in the participants educate result well , with use approach persuasive and judgmental attitude is measured with instrument evaluation the character made by the school